Study of the Population Variability of Two Chrysichthys Species in Six Aquatic Ecosystems in Côte d'Ivoire - T.A.S. Coulibaly; A.B. Adepo-Gourene (European Scientific Journal, ESJ, 2023)
In Côte d'Ivoire, the genus Chrysichthys are subject to intense exploitation pressure and may be threatened by overfishing. The establishment of a sustainable management program for this resource requires in-depth knowledge of this fish. The population relationships were determined by evaluating the morphological variability of the two species of the subgenus Chrysichthys, which was identified in six rivers. Forty-one morphological measurements were carried out on 167 specimens of the species C. maurus and 160 specimens of the species C. nigrodigitatus. These descriptors were subjected to discriminant factor analysis and classification analysis. Within the C. maurus species, specimens from the Bia River and the Aby Lagoon show few morphological differences. These two populations are distinct from the Ebrié Lagoon and the Bandama River. Specimens of the species C. nigrodigitatus can be divided into three distinct groups. The Bia River population occupies an intermediate position between the lot formed by the Agneby River and the Ebrié Lagoon populations and the lot formed by the Bandama River, the Aby Lagoon, and the Grand-Lahou Lagoon populations. Within each lot, the specimens show a great morphological resemblance (similarity). The similarities of the subgenus Chrysichthys could be explained by a potential capacity for exchange of individuals between rivers. The differences between populations would indicate the probable existence of phenotypic plasticity linked to their environment.